Immunostimulatory Effects of Live Lactobacillus sakei K040706 on the CYP-Induced Immunosuppression Mouse Model - Kim, Seo-Yeon (Nutrients, 2020)
Our previous studies have shown that heat-killed Lactobacillus sakei K040706 exerts immunostimulatory and anti-inflammatory activities in macrophages, cyclophosphamide (CYP)-treated mice, and dextran sulfate sodium–induced colitis mice. However, the immunostimulatory effects of live Lactobacillus sakei K040706 (live K040706) against CYP-induced immunosuppression and its underlying molecular mechanisms remain unknown. Therefore, we investigated the immunostimulatory effects of live K040706 (10(8) or 10(9) colony forming unit (CFU)/day, p.o.) in CYP-induced immunosuppressed mice. Oral administration of live K040706 prevented the CYP-induced decreases in body weight, thymus index, natural killer (NK) cell activity, T and B cell proliferation, and cytokine (interferon (IFN)-γ, interleukin (IL)-2, and IL-12) production. The administration of live K040706 also exerted positive effects on the gut microbiota of CYP-induced mice, resulting in a microbiota composition similar to that of normal mice. Moreover, live K040706 significantly enhanced IL-6 and granulocyte-macrophage colony-stimulating factor (GM-CSF) production in the splenocytes and Peyer’s patch (PP) cells of mice and increased bone marrow (BM) cell proliferation. Taken together, our data indicate that live K040706 may effectively accelerate recovery from CYP-induced immunosuppression, leading to activation of the immune system. Therefore, live K040706 may serve as a potential immunomodulatory agent against immunosuppression.